2012
DOI: 10.1371/journal.pone.0042746
|View full text |Cite|
|
Sign up to set email alerts
|

Quetiapine, an Atypical Antipsychotic, Is Protective against Autoimmune-Mediated Demyelination by Inhibiting Effector T Cell Proliferation

Abstract: Quetiapine (Que), a commonly used atypical antipsychotic drug (APD), can prevent myelin from breakdown without immune attack. Multiple sclerosisis (MS), an autoimmune reactive inflammation demyelinating disease, is triggered by activated myelin-specific T lymphocytes (T cells). In this study, we investigated the potential efficacy of Que as an immune-modulating therapeutic agent for experimental autoimmune encephalomyelitis (EAE), a mouse model for MS. Que treatment was initiated on the onset of MOG35–55 pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 36 publications
2
42
0
4
Order By: Relevance
“…(2) QTP inhibited the release of TNF-α from interferon-γ-activated microglia in vitro (Bian et al, 2008); and (3) QTP displayed an immune-modulating role in the experimental autoimmune encephalomyelitis (Mei et al, 2012). In addition, we examined the effect of QTP on the toxic effect of CPZ on the oligodendrocytes (OLs), the myelin-producing cells which are most vulnerable to the toxic effects of CPZ among all the brain cells (Goldberg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(2) QTP inhibited the release of TNF-α from interferon-γ-activated microglia in vitro (Bian et al, 2008); and (3) QTP displayed an immune-modulating role in the experimental autoimmune encephalomyelitis (Mei et al, 2012). In addition, we examined the effect of QTP on the toxic effect of CPZ on the oligodendrocytes (OLs), the myelin-producing cells which are most vulnerable to the toxic effects of CPZ among all the brain cells (Goldberg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that atypical antipsychotics such as risperidone, clozapine, and quetiapine are able to modulate the immune response and reduce disease effectively during EAE [10, 11]; however, the mechanism by which they mediate this effect is not yet fully understood. To better understand this mechanism, we used a dose of 60 mg/kg/day clozapine starting the day before immunization to effectively reduce the disease course of EAE (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the inhibitory e®ect of quetiapine on microglial activation has been described in the cuprizone induced demyelination mouse model (Zhang et al, 2008). Moreover, quetiapine has the potential capacity to reduce microglial and astroglial activation, and decrease myelin-speci¯c T cells in¯ltration (Mei et al, 2012).…”
Section: Cognitive Effects Of Acute Restraint Stress In Male Albino Rmentioning
confidence: 99%